Osteoclasts affect the anti-cancer activity of NK cells - Orrico, Clarissa; Visca, Matteo; Parodi, Monica; Bertolini, Giulia; Mussano, Federico Davide; Ferracini, Riccardo; Roato, Ilaria (Frontiers in Immunology, 2026)
IntroductionNon-small cell lung cancer (NSLSC) stem cells (CSCs) have been shown to be responsible for bone metastasis by interacting with osteoclasts (OCs) and creating an immunosuppressive environment in the bone pre-metastatic niche. Now, we investigated the interaction among OCs, IL-15-stimulated NK cells and CSCs to understand whether NK cells can interfere with the pro-metastatic crosstalk between OCs and CSCs.MethodsIn vitro co-cultures of autologous OCs, NK cells and spheres enriched for CSC from NSCLC A549 cell line (A549/s) were set up both on plastic and bone slices, and OC activity was evaluated through quantification of tartrate-resistant acid phosphatase and of resorption area. The expression of NK cell receptors and ligands was studied through flow cytometry on NK cells, OCs and CSCs. The NK cell degranulation activity was investigated as CD107a expression.ResultsThe number of multinucleated/TRAP+ OCs and TRAP activity decreased when OCs were cultured with NK cells, and with NK cells+A549s. In presence of NK cells, A549s adhered to the bone slice surface and grew, suggesting that NK cells promote the growth of cancer cells rather than block it. Next, we studied whether NK cell phenotype and activity could be modulated by OCs and A549s. When NK cells were co-cultured with A549 cells, OCs, or with the combination of OCs and A549s, we observed a significant increase in the cytotoxic subset of CD56+CD16+ cells, a reduced expression of activating receptors (DNAM-1, NKp44) and an increased expression of inhibitory receptors (TIGIT, TIM3) on NK cells. The NK cell degranulation activity was inhibited by the presence of OCs. The addition of an anti-TIGIT antibody only partially reactivated NK cells, as indicated by a modest control of A549 cell growth, suggesting that NK cell exhaustion was induced by OCs.DiscussionAll together these data show that OCs negatively affect the NK cell cytotoxic activity, allowing the growth of NSCLC CSCs. Our findings reveal a previously unrecognized role of OCs in modulating the immune microenvironment by dampening NK cell function.